2021
DOI: 10.2196/26273
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Social Media, Bedtime Technology Use Rules, and Daytime Sleepiness Among Adolescents: Cross-sectional Findings From a Nationally Representative Sample

Abstract: Background Social media use is associated with poor sleep among adolescents, including daytime sleepiness, which affects adolescents’ mental health. Few studies have examined the associations among specific aspects of social media, such as frequency of checking and posting, perceived importance of social media for social belonging, and daytime sleepiness. Identifying whether certain adolescents are more at risk or protected from the effects of social media on sleepiness may inform future interventi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Children who spent more time on social media were more likely to report having some or a lot of problems on the 5 HRQoL dimensions, and report lower self-rated health than those who spent less time on social media. These findings are in line with previous studies demonstrating that social media use among children aged 13 years and older was inversely associated with HRQoL outcomes such as physical health status and psychological well-being [39,40].…”
Section: Time Spent On Social Media and Hrqolsupporting
confidence: 93%
“…Children who spent more time on social media were more likely to report having some or a lot of problems on the 5 HRQoL dimensions, and report lower self-rated health than those who spent less time on social media. These findings are in line with previous studies demonstrating that social media use among children aged 13 years and older was inversely associated with HRQoL outcomes such as physical health status and psychological well-being [39,40].…”
Section: Time Spent On Social Media and Hrqolsupporting
confidence: 93%
“…For instance, the Hoarding type of OCD triggered people to collect images from the internet and increased their importance of social media [ 42 ]. Also, previous studies showed that there is a significant relationship between checking behavior, social media, and the importance of social media [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The past studies on social media, in the literature, showed us that importance of how social media affects individuals’ way of living and their psychological variables. A study performed on adolescents found that participants’ daytime sleepiness is related to their frequency of use of, and their emphasis on, social media [ 64 ]. The same study also found a significant correlation between the importance of social-media use and participants’ posting on social media and checking (apart from OCD) behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In general, researchers do not know the sleep patterns of social media users unless they recruit them for a study; unfortunately, this means that whatever advantages social media data otherwise affords in terms of scale and passive monitoring are lost to sleep research. A special use case of these data would be for understanding the role of social media use in affecting sleep patterns, which is a topic of significant interest [8][9][10][11][12][13][14]. A recent systematic review concluded that the sleep and social media literature is limited by its reliance on surveys and that for the field to move forward, new study designs are needed [15].…”
Section: Introductionmentioning
confidence: 99%